Facial Transplantation: Nonimmune-Related Hyperacute Graft Failure—The Role of Perfusion Injury. Issue 4 (April 2021) - Santanelli di Pompeo, Fabio; Longo, Benedetto; Giovanoli, Pietro; Plock, Jan Alexander; Campanale, Antonella; Laporta, Rosaria; Sorotos, Michail; Paolini, Guido; Renzi, Luca; Nuccitelli, Gloria; Stoppacciaro, Antonella; Lagana, Bruno; et al.
Abstract : Background: The aim of this study was to report the first case of acute facial allograft transplantation (facial allograft transplantation) failure with allograft removal and autologous free-flap reconstruction. Methods: A 49-year-old female patient affected by neurofibromatosis type 1 with a massive neurofibroma infiltrating the whole left hemiface was planned for FAT for the left hemiface including the auricle, all skin and soft tissues from the temporal region, periorbital and nasal region, and up to the perioral area. The maxillary process of the zygomatic bone, left hemimaxilla, and hemimandible from contralateral parasyphysis to the incisura mandibulae were also included. Results: Total surgical time was 26 hours. There were 2 intraoperative arterial thromboses that were solved with new anastomoses and sufficient flap perfusion. On postoperative day 2, the allograft became pale with suspected arterial occlusion and the patient returned to the operative room for exploration no flow into the FAT was found. The allograft was removed and the recipient site reconstructed with a skin-grafted composite left latissimus dorsi-serratus anterior flap. Conclusions: Hyperacute loss of FAT is a very dramatic event, and the activation of a backup surgical plan is crucial to save patient's life, give a reasonable temporary reconstruction, and return on the waiting-list for a second face transplantation.